PENGARUH Pengaruh Kebijakan Dividen terhadap Harga Saham Perusahaan sektor industrial goods di BEI - Anugrah, Safani; Saputra, Rizqy Imam; Surachman, Ade Elza (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
This study aims to analyze the effect of dividend policy on stock prices in manufacturing companies in the industrial goods sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 period. Using a quantitative approach and secondary data from 12 selected companies through purposive sampling, dividend policy is measured by the Dividend Payout Ratio (DPR), while stock prices are seen from the year-end closing. The results of simple linear regression analysis and T-test so that it can be concluded that dividend policy has a positive and significant effect on stock prices indicating that with T count> T table or 7.505> 2.001 with a significance level of 0.000 <0.05. This finding supports the signal theory that dividends reflect the company's prospects, and provides strategic implications for management in designing dividend policies that are attractive to investors.